Physical demands of tennis across the different court surfaces, performance levels and sexes: a systematic review with meta-analysis - Pluim, B. M.; Jansen, M. G. T.; Williamson, S.; Berry, C.; Camporesi, S.; Fagher, K.; Heron, N.; van Rensburg, D. C. J.; Moreno-Perez, V.; Murray, A.; O'Connor, S. R.; de Oliveira, F. C. L.; et al. (Sports Medicine, 2023)
Background: Tennis is a multidirectional high-intensity intermittent sport for male and female individuals played across multiple surfaces. Although several studies have attempted to characterise the physical demands of tennis, a meta-analysis is still lacking. Objective: We aimed to describe and synthesise the physical demands of tennis across the different court surfaces, performance levels and sexes. Methods: PubMed, Embase, CINAHL and SPORTDiscus were searched from inception to 19 April, 2022. A backward citation search was conducted for included articles using Scopus. The PECOS framework was used to formulate eligibility criteria. Population: tennis players of regional, national or international playing levels (juniors and adults). Exposure: singles match play. Comparison: sex (male/female), court surface (hard, clay, grass). Outcome: duration of play, on-court movement and stroke performance. Study design: cross-sectional, longitudinal. Pooled means or mean differences with 95% confidence intervals were calculated. A random-effects meta-analysis with robust variance estimation was performed. The measures of heterogeneity were Cochrane Q and 95% prediction intervals. Subgroup analysis was used for different court surfaces. Results: The literature search generated 7736 references; 64 articles were included for qualitative and 42 for quantitative review. Mean [95% confidence interval] rally duration, strokes per rally and effective playing time on all surfaces were 5.5 s [4.9, 6.3], 4.1 [3.4, 5.0] and 18.6% [15.8, 21.7] for international male players and 6.4 s [5.4, 7.6], 3.9 [2.4, 6.2] and 20% [17.3, 23.3] for international female players. Mean running distances per point, set and match were 9.6 m [7.6, 12.2], 607 m [443, 832] and 2292 m [1767, 2973] (best-of-5) for international male players and 8.2 m [4.4, 15.2], 574 m [373, 883] and 1249 m [767, 2035] for international female players. Mean first- and second-serve speeds were 182 km·h-1 [178, 187] and 149 km·h-1 [135, 164] for international male players and 156 km·h-1 95% confidence interval [151, 161] and 134 km·h-1 [107, 168] for international female players. Conclusions: The findings from this study provide a comprehensive summary of the physical demands of tennis. These results may guide tennis-specific training programmes. We recommend more consistent measuring and reporting of data to enable future meta-analysts to pool meaningful data.